Carbon Dots–Implanted Graphitic Carbon Nitride Nanosheets for Photocatalysis: Simultaneously Manipulating Carrier Transport in Inter‐ and Intralayers. Issue 4 (24th January 2020) - Han, Mei; Lu, Siyu; Qi, Fei; Zhu, Shoujun; Sun, Haizhu; Yang, Bai
Abstract : Carbon dots (CDs) present unique photoinduced charge transfer and reservoir properties, showing promising application potential in photocatalysis. The in situ preparation of CDs in a graphitic carbon nitride (g‐C3 N4 ) matrix provides not only a new approach for electronic structure modulation and heterostructure construction but also an effective way to improve their photocatalytic performance. However, incorporating CDs into ultrathin g‐C3 N4 remains a challenge. Moreover, simultaneously tuning their carrier transport in inter‐ and intralayers is difficult but significant for their application as efficient photocatalysts. Herein, an unprecedented Se‐chaperoned thermal polymerization method for the synthesis of zero‐dimensional CD‐implanted g‐C3 N4 nanosheets (CCNS) is reported. The CCNS simultaneously facilitate carrier transport and suppress recombination because of the seamless bonding heterostructure of CDs within the in‐plane domains of the g‐C3 N4 nanosheets. Accordingly, the photocatalytic rates of water splitting for H2 evolution and CO2 reduction are enhanced 3.1 and 4.1 times, respectively. In addition, the photocatalytic RhB degradation efficiency dramatically increases 18 times. This work presents a promising solution to solving the current worldwide energy shortage and environmental pollution issues. Abstract : Carbon dots–implanted graphitic carbon nitride nanosheets (CCNS) are prepared via a one‐step Se‐chaperone method. Electronic structure modulation and heterostructure construction are achieved. Notably, the CCNS exhibit enhanced photocatalytic performance for CO2 reduction, water splitting for H2 production, and RhB degradation. There is great potential for its application synchronous energy conversion and environmental remediation.